Analisis Persepsi Wajib Pajak Terhadap Informasi Pajak di Media Sosial Menggunakan Brand24 - Fatimah; Emilla Dwi Nurrahma; Nova Shella Rida Az-Zahra; Muhammad Rikzam Kamal; Nur Anis Nabila Binti Suhaimi (Yayasan Cendekia Gagayunan Indonesia, 2025)
Taxpayers’ perceptions of tax information on social media are highly diverse. This study analyzes these views using a descriptive quantitative approach and Brand24 as a monitoring tool. The research focuses on digital content containing public discussions, with perceptions reflected through social media users’ responses to tax information. The analysis revealed about 45,000 mentions of tax topics, with news media being the main channel, accounting for 28,806 mentions. Accounts like kring_pajak and kumparan_poster were the most active in discussing tax issues, while non-social media accounts such as ranniesaskia had the highest contribution at 3.963%, indicating significant influence. Most content dissemination occurred on TikTok and X platforms, with 2,455 negative mentions increasing by 304% and 2,011 positive mentions rising by 679% from the previous period. Although positive sentiment grew faster percentage-wise, negative sentiment dominance shows ongoing public concerns about taxation. These findings highlight the strategic role of social media in shaping public understanding of tax matters. Consequently, the Directorate General of Taxes (DGT) is advised to develop an integrated social media management strategy to respond to taxpayers promptly and professionally.